Chronic Kidney Disease in Dogs in UK Veterinary Practices: Prevalence, Risk Factors, and Survival. (6th May 2013) - O'Neill, D.G.; Elliott, J.; Church, D.B.; McGreevy, P.D.; Thomson, P.C.; Brodbelt, D.C.
Abstract : Background: The prevalence for chronic kidney disease (CKD) in dogs varies widely (0.05–3.74%). Identified risk factors include advancing age, specific breeds, small body size, and periodontal disease. Hypothesis/Objectives: To estimate the prevalence and identify risk factors associated with CKD diagnosis and survival in dogs. Purebred dogs were hypothesized to have higher CKD risk and poorer survival characteristics than crossbred dogs. Animals: A merged clinical database of 107, 214 dogs attending 89 UK veterinary practices over a 2‐year period (January 2010–December 2011). Methods: A longitudinal study design estimated the apparent prevalence (AP) whereas the true prevalence (TP) was estimated using Bayesian analysis. A nested case‐control study design evaluated risk factors. Survival analysis used the Kaplan‐Meier survival curve method and multivariable Cox proportional hazards regression modeling. Results: The CKD AP was 0.21% (95% CI: 0.19–0.24%) and TP was 0.37% (95% posterior credibility interval 0.02–1.44%). Significant risk factors included increasing age, being insured, and certain breeds (Cocker Spaniel, Cavalier King Charles Spaniel). Cardiac disease was a significant comorbid disorder. Significant clinical signs included halitosis, weight loss, polyuria/polydipsia, urinary incontinence, vomiting, decreased appetite, lethargy, and diarrhea. The median survival time from diagnosis was 226 days (95% CI 112–326 days). International Renal Interest Society stage and blood urea nitrogen concentration at diagnosis were significantly associated with hazard of death due to CKD. Conclusions and Clinical Importance: Chronic kidney disease compromises dog welfare. Increased awareness of CKD risk factors and association of blood biochemistry results with survival time should facilitate diagnosis and optimize case management to improve animal survival and welfare.